Minimally Invasive Methods of Temporary Decompression of the Colon with Obturation Colonic Obstruction: a Literature Review - D. I. Petrov; P. A. Yartsev; D. A. Blagovestnov; V. D. Levitsky; B. T. Tsuleiskiri; I. I. Kirsanov; M. M. Rogal (Неотложная медицинская помощь)
Colorectal cancer is one of the most common oncological diseases. In 40–60% of cases, patients with colorectal cancer enter general surgical hospitals with complications. Obstructive colonic obstruction is the most common complication of colorectal cancer. The radical operation against the background of colonic obstruction is associated with a high postoperative lethality, ranging from 5% to 34%. To improve the results of surgical treatment of patients with colorectal cancer complicated by obturation colonic obstruction, various minimally invasive methods of temporary decompression have been proposed, followed by radical surgery, which signifcantly reduce the risk of complications and mortality.